Modeling and statistical analysis of the impact of environmental factors on aquatic biodiversity - Kozlova Anastasia; Solovieva Tatiana; Kurashkin Sergei; Bricotnin Maxim; Kandaurova Natalia (BIO Web of Conferences)
This work is dedicated to the analysis of aquatic ecosystems and the assessment of the impact of anthropogenic interventions on amphibian biodiversity. Special attention is given to restored and control ponds, where ecological characteristics such as pond type, vegetation cover, shore condition, and the presence of fish are studied, as well as their impact on amphibian species diversity. The work employed correlation, factor, and regression analysis methods, which revealed significant relationships between ecological characteristics and amphibian species abundance. The analysis results show that factors such as pond type, the presence of fish, and shoreline features have a significant impact on species diversity. A positive correlation was found between the presence of amphibian species and overall species diversity, while a negative correlation was observed between anthropogenic factors, such as fish and artificially created ponds, and amphibian abundance. Factor analysis identified latent variables describing the ecological structures of the data, such as pond types, vegetation, and organic sediments, and also demonstrated that the restoration of aquatic ecosystems contributes to improved biodiversity.